2017
DOI: 10.3389/fmicb.2017.01054
|View full text |Cite|
|
Sign up to set email alerts
|

Clostridium chauvoei, an Evolutionary Dead-End Pathogen

Abstract: Full genome sequences of 20 strains of Clostridium chauvoei, the etiological agent of blackleg of cattle and sheep, isolated from four different continents over a period of 64 years (1951–2015) were determined and analyzed. The study reveals that the genome of the species C. chauvoei is highly homogeneous compared to the closely related species C. perfringens, a widespread pathogen that affects human and many animal species. Analysis of the CRISPR locus is sufficient to differentiate most C. chauvoei strains a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
53
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(60 citation statements)
references
References 40 publications
4
53
0
3
Order By: Relevance
“…Recently, the full genome sequences of 20 strains of C. chauvoei, isolated from four different continents over a period of 64 years, were determined and analyzed. The results of this study showed that the strains analyzed were highly conserved, which further indicates that the evolution of C. chauvoei has reached a dead end (RYCHENER et al 2017).…”
Section: Etiology and Virulence Factorsmentioning
confidence: 59%
See 1 more Smart Citation
“…Recently, the full genome sequences of 20 strains of C. chauvoei, isolated from four different continents over a period of 64 years, were determined and analyzed. The results of this study showed that the strains analyzed were highly conserved, which further indicates that the evolution of C. chauvoei has reached a dead end (RYCHENER et al 2017).…”
Section: Etiology and Virulence Factorsmentioning
confidence: 59%
“…The poor protective activity of the recombinant flagellin protein observed previously (KOJIMA et al, 2000) can be attributed to the fact that these authors did not considered that there are a minimum of two copies of fliC gene on the chromosome of C. chauvoei (SASAKI et al, 2002). RYCHENER et al, (2017) found three copies of the allelic variants fliC1, fliC2, and fliC3 of flagellin in most strains studied, thus showing 91.8% amino acid identity with each other in a given strain and 82-96% identity between the paralogues of different strains. THOMAS and collaborators (2017) also revealed the presence of three fliC genes.…”
Section: Cellular Antigensmentioning
confidence: 99%
“…The phylogenetic tree generated (Figure 1(a)) showed family clusters within the clostridiales order. In this tree, the two species of interest belong to the Clostridiaceae family, which includes pathogens that are hazardous to public health [3], and are closely related to unfamiliar species (e.g., C. celatum, C. disporicum, C. chauvoei, and C. sartagoforme) previously recognized as only being pathogenic to non-human animals until less than 10 years ago when they began to be associated with aggressive clinical diseases in humans [82][83][84]. A comparison of the findings based on the traditional 16S rRNA approach (Supplementary Figure S2) showed that the multiple marker method produced the best resolution.…”
Section: Discussionmentioning
confidence: 99%
“…All the genomes included in the dataset defined for each species evaluated were submitted to the aforementioned annotation pipeline. The resultant .gff files were used to define the pan genome with Roary [61], that extracts the coding regions and performs a theoretical translation of aminoacids, then iteratively pre-clustered with CD-HIT 82 and finally make comparisons with BLASTP (considering as threshold a 95% percentage sequence identity). An order of occurrence is generated, in order to define core genome (defined as a gene being in at least 99% of samples) and accessory genome (genes in varying combinations).…”
Section: Intra-taxa Comparisonsmentioning
confidence: 99%
“…Cpf1 endonucleases, some genome editing systems were designed that rely on the endogenous CRISPR array for editing (77)(78)(79). Seventy-four percent of clostridial species harbor CRISPR-Cas loci, including many of the well-studied clostridia (49,(80)(81)(82)(83)(84)(85)(86)(87)(88)(89)(90)(91). Of these, C. pasteurianum and C. tyrobutyricum have developed CRISPR-Cas genome editing systems based on their respective endogenous systems (Fig.…”
Section: Endogenous Crispr Systemsmentioning
confidence: 99%